Supervision of Village Fund Utilization by theRegional Inspectorate in Sekolaq Darat Subdistrict, West Kutai Regency - Yurnalius Meisilianus Setiawan; Muhammad Hairul Saleh; Mohammad Taufik (JGov: Journal of Governmentality, 2025)
This study aims to analyze the supervision conducted by the Regional Inspectorate on the use of village funds in Sekolaq Darat District, West Kutai Regency. The research focuses on identifying the form of supervision, its implementation effectiveness, the challenges faced, and its impact on accountability in village fund management. This is a qualitative study using a case study method. Data were collected through observation, interviews, and documentation. The findings indicate that the Regional Inspectorate of West Kutai has implemented supervision through the WASPADU Program (Integrated Supervision) using assurance dan consulting. The eight villages under supervision generally showed a medium level of financial risk. Common issues found include weak administrative documentation, delayed financial reporting, inactive village supervisory bodies (BPK), and poor management of village-owned enterprises (BUMK). Key challenges in supervision include limited human resources, lack of financial literacy, and internet connectivity problems. Despite these challenges, the supervision has had a positive impact on increasing accountability awareness and encouraging better village governance. The study recommends strengthening the capacity of village officials, digitalizing supervision systems, optimizing the role of BPK, and reforming BUMK management.